Uniform Pricing Against Mill Pricing - Wrede, Matthias (Journal of Regional Science, 2003)
This paper analyzes the co-existence of different pricing strategies. The purpose is to discuss how firms that are limited to uniform pricing affect the outcome of price competition among mill-price-setting firms. Price competition among (three) firms that are restricted to mill pricing is analyzed within the classical Hotelling framework and uniform-price-setting firms are considered as first movers. If uniform-price-setting firms deliver any good, they effectively separate mill-price-setting firms from each other. Finally, it is shown that price competition among first movers strengthens the effects of cross-type-price competition.